Myth and Science Fiction from Fictional Semantics - Ariza Trinidad, Eva (Amaltea. Revista de Mitocrítica, 2020)
The present paper analyses myth and science fiction from fictional semantics, based on the study of the structures of their possible worlds, together with the modal restrictions configurating them, as proposed by Thomas Pavel and Lubomír Doležel. The analysis reveals that many works of prospective science fiction exhibit a structure characteristic of ancient myths — dyadic and with perfectly demarcated domains. Likewise, the hierarchy of modal restrictions configurating them are similar to those found in ancient myths.